Des colonnes pour des vertus dans l’art communal italien du xive siècle - Bertrand Cosnet (Bulletin du Centre d’Études Médiévales d’Auxerre)
Even if the theme of virtues in Christian medieval art has been the subject of numerous studies, which mainly focused on its iconographic tradition and on its allegorical meaning, the very own characteristics of moral values’ pictures have rarely been identified. This study precisely means to highlight an essential property of virtues, that is to say their architectonic characteristic in a figurative register as much as in a symbolic one. In order to do this, it first tries to demonstrate that personification, which is the most common figurative process to show moral values in the Middle Ages, gives virtues a favourable materiality to the link they have with architecture. It then examines the long liturgical, scholastic and poetic tradition that, from Saint Gregory the Great to Saint Thomas Aquinas, establishes a comparison between virtues and constituent elements of ecclesial architecture. The analysis finally focuses, from several precise examples, on the implementation of virtues in sculpted decorations as an architectural support, mainly as columns or caryatids.